SIMULASI NUMERIK KARAKTERISTIK AERODINAMIKA PADA AIRFOIL NACA 4415 DENGAN MEMPERTIMBANGKAN GROUND EFFECT - Hayuningtyas, Rr Saskia Rianasari; Nugroho, Farhan Fathori; Jalaali, Bahrul (Institut Teknologi Dirgantara Adisutjipto, 2023)
Ground effect phenomenon is found when the lift-device such as wing, is placed near the ground. This phenomenon influences the aerodynamics characteristic whereby its appearance is important to be investigated. This work aims to study the influence of ground effect towards aerodynamics characteristion on the NACA4415 airfoil by varying the airfoil’s angle of attack (AoA) as well as the height of ground proximity. Numerical approach conducted on Fluent was carried out while steady assumption, moving wall boundary, and Spalart-Allmaras turbulence model were utilized. The outcomes were aerodynamics characteristic represented by lift and drag coefficients. The results showed that maximum was 1.736 on AoA 15o while maximum was 0.0108 on AoA 18o respectively. It also found that ground proximity also was affecting the values of and . On the height of 0.05 chord, maximum characteristic of lift was obtained while maximum drag was on the 0.8 chord at AoA 18o. It caused by airflow underneath the airfoil was faster due to the ground effect revaling the nozzle-effect, therefore the pressure was higher as according to the Bernoulli’s formulation. On the other hand, drag was related to the vortex generation in which AoA more influental than that of height. This work is hopefully beneficial as initial reference on the Wing-in-Ground (WIG) craft design, in particular on the airfoil selection.